International standards for fetal growth based on serial ultrasound measurements: the Fetal Growth Longitudinal Study of the INTERGROWTH-21st Project. - Papageorghiou, A; Ohuma, E; Altman, D; Todros, T; Cheikh Ismail, L; Lambert, A; Jaffer, Y; Bertino, E; Gravett, MG; Purwar, M; Noble, J; Pang, R; et al. (2014)
BACKGROUND: In 2006, WHO produced international growth standards for infants and children up to age 5 years on the basis of recommendations from a WHO expert committee. Using the same methods and conceptual approach, the Fetal Growth Longitudinal Study (FGLS), part of the INTERGROWTH-21(st) Project, aimed to develop international growth and size standards for fetuses. METHODS: The multicentre, population-based FGLS assessed fetal growth in geographically defined urban populations in eight countries, in which most of the health and nutritional needs of mothers were met and adequate antenatal care was provided. We used ultrasound to take fetal anthropometric measurements prospectively from 14 weeks and 0 days of gestation until birth in a cohort of women with adequate health and nutritional status who were at low risk of intrauterine growth restriction. All women had a reliable estimate of gestational age confirmed by ultrasound measurement of fetal crown-rump length in the first trimester. The five primary ultrasound measures of fetal growth--head circumference, biparietal diameter, occipitofrontal diameter, abdominal circumference, and femur length--were obtained every 5 weeks (within 1 week either side) from 14 weeks to 42 weeks of gestation. The best fitting curves for the five measures were selected using second-degree fractional polynomials and further modelled in a multilevel framework to account for the longitudinal design of the study. FINDINGS: We screened 13,108 women commencing antenatal care at less than 14 weeks and 0 days of gestation, of whom 4607 (35%) were eligible. 4321 (94%) eligible women had pregnancies without major complications and delivered live singletons without congenital malformations (the analysis population). We documented very low maternal and perinatal mortality and morbidity, confirming that the participants were at low risk of adverse outcomes. For each of the five fetal growth measures, the mean differences between the observed and smoothed centiles for the 3rd, 50th, and 97th centiles, respectively, were small: 2·25 mm (SD 3·0), 0·02 mm (3·0), and -2·69 mm (3·2) for head circumference; 0·83 mm (0·9), -0·05 mm (0·8), and -0·84 mm (1·0) for biparietal diameter; 0·63 mm (1·2), 0·04 mm (1·1), and -1·05 mm (1·3) for occipitofrontal diameter; 2·99 mm (3·1), 0·25 mm (3·2), and -4·22 mm (3·7) for abdominal circumference; and 0·62 mm (0·8), 0·03 mm (0·8), and -0·65 mm (0·8) for femur length. We calculated the 3rd, 5th 10th, 50th, 90th, 95th and 97th centile curves according to gestational age for these ultrasound measures, representing the international standards for fetal growth. INTERPRETATION: We recommend these international fetal growth standards for the clinical interpretation of routinely taken ultrasound measurements and for comparisons across populations. FUNDING: Bill and Melinda Gates Foundation.